Analysis of German nutrition brochures for pregnant women with evidence-based patient information criteria. Issue 2 (February 2015) - Küllenberg de Gaudry, Daniela; Grede, Nina; Motschall, Edith; Lins, Sabine
Highlights: More research on the risk of salmonellosis, toxoplasmosis or listeriosis in Germany is needed. Few brochures gave a risk description, predominantly verbally (which is often overestimated). German nutrition brochures for pregnant women should be adapted to comply with EBPI criteria. High quality nutrition brochures are needed to facilitate an informed patient choice. Abstract: Objective : To evaluate nutrition brochures for pregnant women in Germany based on evidence-based patient information (EBPI) criteria. Methods : Nutrition brochures for pregnant women in Germany were collected. Brochures addressing the risk of salmonellosis, toxoplasmosis or listeriosis were analyzed by two researchers independently. Results : Fifty brochures reporting any information on the risk of infection were analyzed. Most brochures did not include literature citations and only few brochures gave a risk description, predominantly verbally, which usually leads to an overestimation of the actual risk. Advertisement was present in 22% of the brochures. Conclusion : German nutrition brochures for pregnant women should be adapted to comply with evidence-based patient information (EBPI) criteria for achieving a better quality of the disseminated information. Practice implications : The findings highlight the need of high quality nutrition brochures for pregnant women, which are relevant not only for pregnant women, but also to those responsible for creating brochures, and to physicians in charge of patient information.